Desain Perancangan E-Commerce Kain Tenun Lombok Desa Sukarara Lombok Tengah - Suriyati Suriyati (Universitas Andi Djemma, 2019)
Lombok is songket woven fabric which has embossed on cotton yarn, threads of silver or gold thread. Songket weaving craft that is learned by the women Sasak is a type of traditional weaving craft. Starting from the yarn manufacturing, dyeing, to the manufacture of woven fabrics, all done the old fashioned way. To make a yarn that will be used for weaving using natural materials, such as fiber pineapple, banana fiber, cotton, and bark. As for the dye, using natural dyes from ingredients that are also naturally anyway. To produce songket cloth of a width of 1.2 m and 2 m in length takes 2-4 weeks. Motif used in the manufacture of songket is a legacy handed down that are not allowed to diseberluaskan. It is said that the traditional songket motifs from village Lombok Sukarara reached more than 100 patterns. Nothing is recorded or drawn details, unless stored in the form of a master to learn generations to come. This study uses qualitative research aimed at understanding more deeply to a problem that is studied. This study investigates the problems in marketing and promoting traditional handicrafts woven Sasak by breaking factor in using fishbone diagrams. Woven Songket generated Lombok society is very unique, because here there is a meeting of western and eastern. Technically, the second meeting of the area led to the integration in other areas in Indonesia that did not exist. Along with the development, songket cloth or woven cloth Lombok has developed the idea, both in terms of the motive and the enrichment of the author, to give birth to works of Neat and very attractive to domestic and foreign tourists. Innovation targeted in this study is an application of e-commerce in helping to market, promote and manage sales songket online.